RANCANG BANGUN APLIKASI WEBSITE E-LEARNING PADA SMK RESPATI 1 JAKARTA - Nanang Nuryadi (Universitas Bina Sarana Informatika, 2018)
Abstract - Information technology today is needed in various fields, be it the field of health, business, and education. A real example of the use of information technology in the world of education is E-Learning, as the development of Internet technology E-Learning began to be developed, true E-Learning is a form of conventional learning is poured in digital format through internet technology. SMK Respati 1 is an accredited Vocational High School B under the auspices of the Respati Culture and Education Foundation. In terms of teaching and learning activities SMK Respati 1 still using the system of teaching and learning in a conventional way, it causes difficulties for students and teachers in accessing information from school subjects terurama terurama. In building this system the author uses PHP programming language with MySQL database. With this e-learning system is expected to assist the school, especially teachers and students in teaching and learning activities